APLIKASI PERMAINAN BISNIS “SIKLUS USAHA DASAR” DALAM PEMBELAJARAN KEWIRAUSAHAAN DI ITB NOBEL INDONESIA - Bahrul Ulum Ilham; Ahmad Firman; Fitriani Latief; Mariah (AkMen JURNAL ILMIAH, 2023)
This research examines the application of the "basic business cycle" business simulation in entrepreneurship learning at ITB Nobel Indonesia, Makassar City. This business game simulation is the first of three "Start and Improve Your Business" modules developed by the International Labor organization (ILO). This research uses a mixed method, namely quantitative descriptive, by obtaining data in the form of numbers and qualitative descriptive to explain phenomena that occur in the classroom during and after the game simulation is completed. This research was conducted on 40 ITB Nobel Makassar students using questionnaires and direct observation during the game. From the business game simulation results, students stated that this game provided `practical' experience in carrying out business simulations in class. Students can also discuss with each other how to make decisions and face the consequences that they have to do, especially the best use of capital in business. From the quantitative results of this research, the entrepreneurship learning plan through business game simulations can generally be achieved with the answer choices being firmly agreed, above 60% and above 30% who agree, and no one who disagrees or strongly disagrees. Entrepreneurship learning through business simulation games is practical because it uses experience-based learning tools where students learn business processes by running a simulated company in a risk-free, interactive, and realistic environment..